Modeling the Dynamic Evolution of the Vehicular Ad Hoc Networks under the City Scenario - Lili Zhang; Yueheng Li; Guoping Tan; Rongbo Zhu; Hao Chen (International Journal of Distributed Sensor Networks)
Nowadays, vehicular ad hoc network (VANET) has attracted more and more attention due to its various applications to improve the road traffic safety and efficiency. So there were plenty of exploration work and merit on the intervehicle communication, routing, and data forwarding, but it is not easy to design the efficient routing and data forwarding algorithm, because it is hard to understand the dynamic evolution of its network topology due to the fast movement of the vehicles in the network. While the network evolution structure is the key to design the optimal data forwarding strategy, hence, in this paper, we will analyze the dynamic evolution of topology characteristics based on the real data collected by the GPS devices installed on vehicles and then model the network evolution by the dynamic topology characteristics. In the end, we analyze and verify the efficiency of our model by theoretical deductions and simulations, and our model will be helpful to find more efficient routing algorithm and build the more trustable simulator of VANET.